Local Wisdom, Local Culture, and Global Market Post-Pandemic Covid-19: Rebranding the City of Tuban, Indonesia - Santi Isnaini; Dina Septiani; Satrya Wibawa; Aqila Nur Rahmalia (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2024)
This study aims to describe the implementation of local wisdom in the imaging strategy of Tuban, East Java, after the Covid-19 pandemic. It is crucial to explore the understanding of implementing local wisdom in the imaging strategy of Tuban, East Java, after the COVID-19 pandemic. In this study, the theories used include the theory of city branding, city imaging strategies, and local wisdom. These three theories become the basis for understanding and explaining the implementation of local wisdom in the imaging strategy of the city of Tuban, East Java. The results showed that Tuban Regency carried out various city imaging efforts. Implementing local wisdom in urban imaging strategies includes history, processes, stakeholders, city branding elements, and events. The research model on the implementation of local wisdom in the imaging strategy of Tuban City is closely related to history, which includes branding initiatives in the city vision, tradition and culture, city regulations, and city vision.